2008
DOI: 10.1261/rna.780708
|View full text |Cite
|
Sign up to set email alerts
|

Identification of PCBP2, a facilitator of IRES-mediated translation, as a novel constituent of stress granules and processing bodies

Abstract: Recent advances in microscopic techniques have shed light on the roles of specific subcellular structures in the regulation of gene expression. One such structure is the stress granule (SG), which is engaged in stress-triggered translational arrest by sequestering pre-initiation complexes of translation. Recent studies revealed the spatial, compositional, and functional linkage of the SG to the processing body (P-body), another cytoplasmic structure that has been implicated in mRNA degradation and siRNA-or miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 17 publications
5
47
0
1
Order By: Relevance
“…The sequence of TUC338 overlaps with that of PCBP2, an RNA binding protein involved in mRNA processing in humans (40)(41)(42). Interestingly, exonic ultraconserved regions are frequently associated with RNA processing, such as RNA binding or RNA splicing, suggesting a potential role as regulators of RNA.…”
Section: Discussionmentioning
confidence: 99%
“…The sequence of TUC338 overlaps with that of PCBP2, an RNA binding protein involved in mRNA processing in humans (40)(41)(42). Interestingly, exonic ultraconserved regions are frequently associated with RNA processing, such as RNA binding or RNA splicing, suggesting a potential role as regulators of RNA.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it is possible that release is triggered by as-yet-unidentified mechanisms, followed soon thereafter by cleavage. Interestingly, PCBP-2, an RNA binding protein that plays an important role in translation and replication of the viral RNA genome, was recently shown to be recruited to SGs during heat shock and oxidative stress (3,15,16,39,49). As PCBP2 is also cleaved by the viral 3C protease (41), it will be interesting to see if it also is initially recruited and then released from poliovirus-induced SGs.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence recovery after photobleaching (FRAP) experiments revealed that many components cycle rapidly in and out of PBs and SGs, although a subset are more static (Aizer et al, 2008;Andrei et al, 2005;Eisinger-Mathason et al, 2008;Fujimura et al, 2008a;Fujimura et al, 2008b;Guil et al, 2006;Kedersha et al, 2000;Kedersha et al, 2005;Leung et al, 2006;Mollet et al, 2008). Realtime imaging of human cell lines shows that most PBs and SGs move in an apparently random manner.…”
Section: Morphology and Movement Of Pbs And Sgsmentioning
confidence: 99%
“…FRAP experiments show that many factors rapidly cycle in and out of PBs (Aizer et al, 2008;Andrei et al, 2005;Fujimura et al, 2008b;Kedersha et al, 2005;Leung et al, 2006), and PBs rapidly disappear when new mRNPs are prevented from entering PBs upon treatment of S. cerevisiae, Drosophila or human cells with translation elongation inhibitors (Cougot et al, 2004;Eulalio et al, 2007b;Teixeira et al, 2005). Evidence suggests that the release of mRNPs from PBs involves either mRNA decay or release of the mRNP back into translation.…”
Section: Release Of Mrnps From Pbsmentioning
confidence: 99%